Correction: Investigation of high contrast and reversible luminescence thermochromism of the quantum confined Cs4PbBr6 perovskite solid. Issue 12 (13th March 2019) - Choi, Jin Woo; Cho, Namchul; Woo, Hee Chul; Oh, Byeong M.; Almutlaq, Jawaher; Bakr, Osman M.; Kim, Sung-Hoon; Lee, Chang-Lyoul; Kim, Jong H.
Abstract : Correction for 'Investigation of high contrast and reversible luminescence thermochromism of the quantum confined Cs4 PbBr6 perovskite solid' by Jong H. Kim et al., Nanoscale, 2019, DOI: 10.1039/c8nr10223f.